Politicization of a disaster and victim blaming: Analysis of the Sewol ferry case in Korea. (1st February 2022) - Chung, Ji-Bum; Choi, Eugene; Kim, Leo; Kim, Byeong Je
Abstract: This study aimed to analyze the public perception of disaster victims through survey and media analyses. To compare the impact of the politicization of disasters, we examined three disaster cases that had a major impact on Korean society: the Sewol ferry tragedy, the Cheonan warship sinking accident, and the Humidifier disinfectant disaster. A comparative regression analysis showed that the Sewol ferry tragedy had strong political biases compared to the others. From a media big data analysis, the criticism to the Sewol victims intensified following the impeachment of President Park Geun-hye and the inauguration of a new government, both in number and discursive power. We concluded that legitimization theory can successfully explain this victim blaming mechanism. Conservative respondents blamed the Sewol ferry victims more because they had a strong tendency to defend the politically conservative regime of Korean society to maintain the traditional power landscape.